HUBUNGAN AKTIVITAS FISIK DENGAN KUALITAS TIDUR PADA SISWA KELAS X IPA 2 DI SMA NEGERI 1 KOTO GASIB - M. Rasyid Khatami; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Health is an important element in human life. In conditions of physical and spiritual health, humans can carry out activities optimally. To get good physical and spiritual health, it is necessary to maintain regular health care. Some efforts to maintain health are by doing physical activity and maintaining sleep quality. The purpose of this study was to find out whether there is a relationship between physical activity and sleep quality in class X IPA 2 students at SMA Negeri 1 Koto Gasib. This research is a type of research correlation. The sample in this study consisted of 25 class X IPA 2 students. Collecting data to determine the level of physical activity of students was obtained from filling out the questionnaire Physical Activity Questionnaire for Adolescents (PAQ-A), while to find out the level of students' sleep quality was obtained from filling out the Pittsburgh Sleep Quality Index (PSQI) questionnaire which was given directly to students then data analysis and hypothesis testing were carried out using the parametric statistical method Pearson Product Correlation Coefficient -Moment (Pearson Product-Moment Correlation Coefficient) in SPSS 26 For Windows. The results found in this study are there 7 (28%) students' physical activity was in the moderate category, and 18 (72%) students were in the low category, then there were 11 (44%) students with good sleep quality and 14 (56%) students with poor sleep quality. The results of data analysis found that the value of rx.y = 0.569, and rx.y = 0.569 > r table: 0.505. Based on the results of this study the level of association of 0.569 was at the